TP53 co-mutations in advanced lung adenocarcinoma: comparative bioinformatic analyses suggest ambivalent character on overall survival alongside KRAS, STK11 and KEAP1 mutations - Frille, Armin; Boeschen, Myriam; Wirtz, Hubert; Stiller, Mathias; Bläker, Hendrik; von Laffert, Maximilian (Frontiers in Oncology, 2024)
Background: Recently, we could show that the co-mutations of KRAS + KEAP1, STK11 + KEAP1 and KRAS + STK11 + KEAP1 lead to a significantly shorter median overall survival (mOS) across treatments by analyzing multiple datasets. TP53, a tumor suppressor gene, plays a crucial role in regulating cell cycle progression. Its mutations occur in approximately 40-50% of non-small lung cancer (NSCLC). Co-occurrence of all four mentioned mutations has been a matter of debate for years. The aim of this study was to assess the distribution of these four mutations and the influence of the different co-mutational patterns on survival. Methods: We present a comparative bioinformatic analysis and refer to data of 4,109 patients with lung adenocarcinoma (LUAD). Results: Most of the mutations within the LUAD belong to TP53-only (29.0%), quadruple- negative (25.9%) and KRAS-only (13.4%). Whereas TP53-mutations seem to have protective effects in the context of further KEAP1- and KRAS + KEAP1-alterations (improved mOS), their role seems contrary if acquired in an already existing combination of mutations as KRAS + STK11, KRAS + STK11 + KEAP1 and STK1 + KEAP1. TP53 had a negative influence on KRAS- only mutated LUAD (mOS reduced significantly by more than 30%). Discussion: These data underline the need for complex mutational testing to estimate prognosis more accurately in patients with advanced LUAD.